Coopetition: a fundamental feature of entrepreneurial firms' collaborative dynamics. Issue 7 (5th August 2019) - McGrath, Helen; O'Toole, Thomas; Canning, Louise
Abstract : Purpose: This paper aims to explore coopetition as a fundamental feature of the collaborative dynamics inherent in entrepreneurial ventures. The authors present a conceptual model and definition of entrepreneurial coopetition, the latter being explained as entrepreneurial involvement in simultaneous cooperative and competitive interactions with business network actors in a relational environment. Design/methodology/approach: Using the micro-brewing industry in a Southern State in the USA, as an empirical base, the authors use an abductive case study approach drawing from multiple data sources including semi-structured interviews, marketing materials, information available on websites and social media, as well as information contained in newspaper articles and policy documents. Findings: Findings suggest that entrepreneurs habitually interact in a coopetitive manner through norms formed in interaction and that these are often in response to the environment. Research limitations/implications: Findings are limited to one particular context. Future research could include entrepreneurs from other sectors, state or country contexts which may reveal other coopetition themes. Practical implications: More benefits in coopetition could be reaped if the entrepreneur were more cognitively aware of, and strategically planned for, the coopetitive processes in which they are (or could be) engaged. Originality/value: The authors open the black box of entrepreneurial coopetition by putting forward and empirically examining a conceptual definition of entrepreneurial coopetition. This work moves the coopetition discussion beyond the motives behind and consequences of coopetition, analysing interactions from a process perspective. The authors respond to recent calls for a deeper understanding of coopetitive mind-sets and a multilevel approach to coopetition.